AVALIAÇÃO DO DESEMPENHO ENERGÉTICO DE FACHADAS: SIMULAÇÃO DE EDIFÍCIO COMERCIAL EM DIFERENTES ZONAS BIOCLIMÁTICAS BRASILEIRAS - Andrade, Marco Túlio Barbosa; Ferreira, Camila Carvalho; Hirashima, Simone Queiroz da Silveira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study aimed to analyze the influence of façades on energy demand for air conditioning of commercial buildings located in different Brazilian bioclimatic zones. In total 132 scenarios were simulated using the software DesignBuilder, considering 4 façades types, 3 building sizes and 11 cities, located in seven distinct bioclimatic zones, as parameters. Results highlighted that the climatic conditions play an important role on air conditioning demand. Among the façade types studied, the white painting had the best energetic performance, followed by ventilated façades in aluminum composite material (ACM) and red granite and finally the black painting. In each case, the heat gains were related to the material absorptance and emissivity and to the air flux dynamics inside the ventilated cavities. Also, the increase of building dimensions led to a reduction of energy demand per area, related to the increase of air volume in the internal environment, and to a reduction of façade influence, due to the increase of roofing influence and internal heat gains (equipment, lighting and human metabolism).